Bright six-partite entanglement from coupled intracavity nondegenerate parametric down-conversion. (20th March 2017) - Wang, Junfeng; Ma, Luwei; Chen, Jinglin; Wu, Hongyan; Liu, Yuzhu; Wang, Enhui; Yan, Qing; She, Yuan
Abstract: We propose an experimentally feasible scheme to produce bright six-partite continuous-variable (CV) entanglement by coupled intracavity non-degenerate parametric down-conversion operating above-threshold. The six-partite entanglement properties of the output fields are theoretically analyzed according to the sufficient inseparability criterion for multipartite CV entanglement. Such compact tunable multipartite CV entanglement, generated from a coupled system, could be used in quantum communications and networks.